2016
DOI: 10.1177/2158244016677569
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Effect of Expression Intensity on Evaluations of Facial Attractiveness

Abstract: Many studies have shown that facial expression influences evaluations of attractiveness, but the effect of expression intensity remains unclear. In the present study, participants rated the expression intensity and attractiveness of faces with happy, neutral, or sad expressions. Sad faces, as anticipated, were judged as less attractive than neutral and happy faces. Among happy expressions, faces with more intense expressions were considered more attractive; for sad expressions, there was no significant relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
(52 reference statements)
2
14
0
Order By: Relevance
“…For example, the degree of symmetry affects facial attractiveness, but a greater preference for facial symmetry has been shown to arise when faces were upright than when they were inverted (Little and Jones, 2003). A happy facial expression, such as a smile, enhances perceived attractiveness (Golle et al, 2014;Ueda et al, 2016), but recognition of facial expressions is also disrupted by face inversion (Sugase-Miyamoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the degree of symmetry affects facial attractiveness, but a greater preference for facial symmetry has been shown to arise when faces were upright than when they were inverted (Little and Jones, 2003). A happy facial expression, such as a smile, enhances perceived attractiveness (Golle et al, 2014;Ueda et al, 2016), but recognition of facial expressions is also disrupted by face inversion (Sugase-Miyamoto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous research has suggested that these evaluative dimensions are interrelated and may vary according to the facial expression (for a review, see Garrido et al, 2016 ). For example, the same model is perceived as more attractive when displaying a happy expression than when displaying a sad ( Mueser et al, 1984 ; Ueda et al, 2016 ) or angry ( Morrison et al, 2013 ) expression. Indeed, the relationship between attractiveness and happiness seems to be bidirectional – the ratings of attractiveness are influenced by the intensity of the smile and attractive faces are more easily recognized as happy ( Golle et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the relationship between attractiveness and happiness seems to be bidirectional – the ratings of attractiveness are influenced by the intensity of the smile and attractive faces are more easily recognized as happy ( Golle et al, 2014 ). It is noteworthy that the intensity of positive and negative expressions asymmetrically influences attractiveness evaluations, such that faces with more intense happy expressions are deemed more attractive, whereas no significant relationship between attractiveness and intensity emerges for sad expressions ( Ueda et al, 2016 ). Familiarity also influences the perception of facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that positive and negative expressions asymmetrically influence the evaluations of facial attractiveness. Sad faces were found to be rated as less attractive than neutral or happy faces (Mueser, Grau, Sussman, & Rosen, ; Ueda, Kuraguchi, & Ashida, ), and angry faces were also reported to discount the attractiveness bias, to some extent (Jaensch et al, ). In contrast, smiling faces were rated as more attractive and having more positive personality traits than neutral faces (Berscheid & Walster, ; Magda & Goodwin, ; Mehu, Little, & Dunbar, ).…”
mentioning
confidence: 99%